ANALISIS PENGUKURAN EFISIENSI OPERASIONAL BANK MANDIRI DAN BANK TABUNGAN NEGARA - Wiyati, Rita (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2016)
The purpose of this study were: to analyze the operational efficiency of the Bank and the State Savings Bank. Types of data collected in this research is quantitative data. The data sources used are: existing data are reported the State Savings bank finance. The data used in this study were obtained from published reports compiled by Bank Indonesia in the Indonesian banking directory and publications by the bank concerned over the internet. The analytical method used in this research are: quantitative analysis method of non-parametric DEA (Data Envelopment Analysis). DEA efficiency measurements by using the software Data Envelopment Analysis Program (DEAP version 2.1) .Berdasarkan seraca public research operations of the two banks (Bank Mandiri and BTN) is said to be efficient based on calculations using software DEA.Hasil DEA value calculation CRSTE and bank VRSTE Mandiri and bank BTN from 2011 through 2014 show the number 1. It is expected for the two banks, namely bank Mandiri and bank BTN, must constantly seek new innovations related to its operations, especially Mandiri bank. Although independent bank asset growth, equity and net income but independent banks has decreased, in generating other operating income, operating income means that independent banks still rely on income derived from interest instead of other operating income.